2018
DOI: 10.1002/bdd.2119
|View full text |Cite
|
Sign up to set email alerts
|

Application of a physiologically‐based pharmacokinetic model for the prediction of bumetanide plasma and brain concentrations in the neonate

Abstract: Bumetanide is a loop diuretic that is proposed to possess a beneficial effect on disorders of the central nervous system, including neonatal seizures. Therefore, prediction of unbound bumetanide concentrations in the brain is relevant from a pharmacological prospective. A physiologically-based pharmacokinetic (PBPK) model was developed for the prediction of bumetanide disposition in plasma and brain in adult and paediatric populations. A compound file was built for bumetanide integrating physicochemical data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The development of PBPK models for psychoactive drugs (and other drugs that can penetrate the BBB), particularly when they are subject to active uptake or efflux, is therefore dependent on robust and reliable measurement of the abundances of BBB transporters in humans as well as animal species used in pre-clinical studies (Ball et al 2014;Gaohua et al 2016). Recent applications of such PBPK models also highlight their potential in assessing the needs of subpopulations, which are not fully explored in clinical studies (e.g., pediatrics, brain cancer patients) as reported previously (Spanakis et al 2016;Kalluri et al 2017;Donovan et al 2018).…”
Section: Discussionmentioning
confidence: 97%
“…The development of PBPK models for psychoactive drugs (and other drugs that can penetrate the BBB), particularly when they are subject to active uptake or efflux, is therefore dependent on robust and reliable measurement of the abundances of BBB transporters in humans as well as animal species used in pre-clinical studies (Ball et al 2014;Gaohua et al 2016). Recent applications of such PBPK models also highlight their potential in assessing the needs of subpopulations, which are not fully explored in clinical studies (e.g., pediatrics, brain cancer patients) as reported previously (Spanakis et al 2016;Kalluri et al 2017;Donovan et al 2018).…”
Section: Discussionmentioning
confidence: 97%
“…There are also advantages to the use of in silico models to predict outcome from a variety of inputs, possibly by combining microbiota metabolism rates with host drug absorption and metabolic rates. Specifically adapting many of the emerging physiologically based pharmacokinetic models, which predict drug levels in tissues based on a variety of drug and host parameters (Min and Bae, 2017;Thiele et al, 2017;Donovan et al, 2018), to allow for greater contribution of microbiota-mediated metabolism, may be a useful approach to predict overall clinical impact.…”
Section: Experimental Approaches In Pharmacomicrobiomicsmentioning
confidence: 99%
“…A model using pediatric methotrexate data included digitized CSF and brain extracellular fluid concentrations and found that, although the model accurately characterized methotrexate's CNS distribution in rats, dogs, and human adults, it underestimated CNS concentrations in critically ill children aged 2–17 years . An additional PBPK model of bumetanide was developed using adult plasma data and scaled to various pediatric populations . It accurately predicted plasma concentrations for all infants except critically ill neonates, and it did not evaluate the model's CNS distribution predictions with CSF samples .…”
Section: Discussionmentioning
confidence: 99%
“…An additional PBPK model of bumetanide was developed using adult plasma data and scaled to various pediatric populations . It accurately predicted plasma concentrations for all infants except critically ill neonates, and it did not evaluate the model's CNS distribution predictions with CSF samples . Our model was developed using numerous plasma samples from preterm and term infants, many from a preterm population receiving the drug prophylactically.…”
Section: Discussionmentioning
confidence: 99%